Primary cilia are critical for Sonic Hedgehog-mediated dopaminergic neurogenesis in the embryonic midbrain - Gazea, Mary; Tasouri, Evangelia; Gojak, Christian P.; Kurtulmus, Bahtiyar; Spatz, Joachim P.; Pereira, Gislene (Developmental biology, 2016)
Midbrain dopaminergic (mDA) neurons modulate various motor and cognitive functions, and their dysfunction or degeneration has been implicated in several psychiatric diseases. Both Sonic Hedgehog (Shh) and Wnt signaling pathways have been shown to be essential for normal development of mDA neurons. Primary cilia are critical for the development of a number of structures in the brain by serving as a hub for essential developmental signaling cascades, but their role in the generation of mDA neurons has not been examined. We analyzed mutant mouse lines deficient in the intraflagellar transport protein IFT88, which is critical for primary cilia function. Conditional inactivation of Ift88 in the midbrain after E9.0 results in progressive loss of primary cilia, a decreased size of the mDA progenitor domain, and a reduction in mDA neurons. We identified Shh signaling as the primary cause of these defects, since conditional inactivation of the Shh signaling pathway after E9.0, through genetic ablation of Gli2 and Gli3 in the midbrain, results in a phenotype basically identical to the one seen in Ift88 conditional mutants. Moreover, the expansion of the mDA progenitor domain observed when Shh signaling is constitutively activated does not occur in absence of Ift88. In contrast, clusters of Shh-responding progenitors are maintained in the ventral midbrain of the hypomorphic Ift88 mouse mutant, cobblestone. Despite the residual Shh signaling, the integrity of the mDA progenitor domain is severely disturbed, and consequently very few mDA neurons are generated in cobblestone mutants. Our results identify for the first time a crucial role of primary cilia in the induction of mDA progenitors, define a narrow time window in which Shh-mediated signaling is dependent upon normal primary cilia function for this purpose, and suggest that later Wnt signaling-dependent events act independently of primary cilia.